Global insect decline is the result of wilful political failure: A battle plan for entomology. Issue 10 (12th October 2022) - Donkersley, Philip; Ashton, Louise; Lamarre, Greg P. A.; Segar, Simon
Abstract: The Millennium Ecosystem Assessment assessed ecosystem change, human wellbeing and scientific evidence for sustainable use of biological systems. Despite intergovernmental acknowledgement of the problem, global ecological decline has continued, including declines in insect biodiversity, which has received much media attention in recent years. Several roadmaps to averting biological declines have failed due to various economic and political factors, and so biodiversity loss continues, driven by several interacting human pressures. Humans are innately linked with nature but tend to take it for granted. The benefits we gain from the insect world are broad, yet aversion or phobias of invertebrates are common, and stand firmly in the path of their successful conservation. Providing an integrated synthesis for policy teams, conservation NGOs, academic researchers and those interested in public engagement, this article considers: (1) The lack of progress to preserve and protect insects. (2) Examples relating to insect decline and contributions insects make to people worldwide, and consequently what we stand to lose. (3) How to engage the public, governmental organizations and researchers through "insect contributions to people" to better address insect declines. International political will has consistently acknowledged the existence of biodiversity decline, but apart from a few narrow cases of charismatic megafauna, little meaningful change has been achieved. Public values are reflected in political willpower, the progress being made across the world, changing views on insects in the public should initiate a much‐needed political sea‐change. Taking both existing activity and required future actions, we outline an entomologist's "battle plan" to enormously expand our efforts and become the champions of insect conservation that the natural world needs. Abstract : As a subject of substantial research and media attention, the "Insect Armageddon" is both timely and somewhat controversial. Published studies argue back and forth over the extent of insect declines worldwide. Little attention has been given over what we stand to lose, should we as a species continue to ignore global insect biodiversity loss. We present a battle plan for entomologists to confront this loss and engage the world in saving insects for the benefit of all.